Lack of simian immunodeficiency virus (SIV) specific IgA response in the intestine of SIV infected rhesus macaques. Issue 5 (1st May 2002) - Schäfer, F; Kewenig, S; Stolte, N; Stahl-Hennig, C; Stallmach, A; Kaup, F-J; Zeitz, M; Schneider, T
Abstract : Background: Little is known about secretory immunity—the major defence mechanism at mucosal surfaces—in human immunodeficiency virus (HIV) infected patients, especially in the early stages of the disease. Aims: The aim of the study was to analyse mucosal immunoglobulin production and simian immunodeficiency virus (SIV) specific antibody response in the intestinal mucosa during the course of SIV infection in comparison with serum and saliva. Animals and methods: IgG, IgA, and IgM concentrations were determined in supernatants of short term cultured duodenal biopsies, serum, and saliva from SIV infected rhesus macaques (n=8) and controls (n=2) by ELISA at defined times before and after infection. Specific antibodies to SIV were detected by western blot and/or dot blot analysis. In addition, rectal swabs from two uninfected and 12 SIV infected rhesus macaques (seven without and five with enteritis) were analysed for albumin and IgG concentrations. Results: An increase in total intestinal IgG and a decrease in IgA were observed. SIV specific IgG or IgA responses were detectable as early as one week after SIV infection in the serum of seven of eight animals. In contrast, intestinal SIV specific IgG production was detected only four weeks after infection in six of eight animals, and intestinal SIV specific IgA was not produced in the intestine at any time point. In saliva, the secretory component on SIV specific IgA was only detected in one animal at week 24 after infection. Enteritis is frequent in SIV infected animals and results in a significant increase in albumin and IgG secretion into the intestinal lumen. Conclusion: Despite modest quantitative changes in mucosal immunglobulin production there was a total lack of SIV specific IgA synthesis in the intestine during SIV infection. This lack or disturbed secretory SIV specific IgA response at mucosal surfaces may explain the rapid and high HIV/SIV replication in this compartment. In addition, our investigations indicate secretion of serum proteins into intestinal fluids during SIV infection. Previous investigations using intestinal secretions or swabs for analysing quantitative and specific immunglobulins therefore should be interpreted with caution.